2020
DOI: 10.3233/nre-203133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trunk stabilization exercise on abdominal muscle thickness, balance and gait abilities of patients with hemiplegic stroke: A randomized controlled trial

Abstract: BACKGROUND: Trunk stability has been identified as an important prerequisite of functional movement. OBJECTIVE: To investigate the effectiveness of core muscle contraction training on abdominal muscle thickness, balance, and gait ability in stroke patients. METHODS: Thirty patients with stroke were randomly assigned to two experimental groups and a control group. All groups received conventional therapeutic exercise program for six weeks. The experimental groups additionally trained trunk stability exercise wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that upper limb task training with abdominal cramps (i.e., active stabilization of the trunk) improved gait and balance in patients with hemiparesis [ 42 , 43 ]. On the other hand, the influence of passive trunk and shoulder stabilization on hand and wrist movement has been rarely analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that upper limb task training with abdominal cramps (i.e., active stabilization of the trunk) improved gait and balance in patients with hemiparesis [ 42 , 43 ]. On the other hand, the influence of passive trunk and shoulder stabilization on hand and wrist movement has been rarely analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on trunk muscle training for improving trunk function showed favourable results in both sub-acute and chronic stroke patients, with a duration of intervention ranging between two to eight weeks. Rehabilitative approaches targeting trunk function in stroke included specific trunk training exercises (TTE), trunk training exercises with a modality, Bobath approach/Neurodevelopmental Treatment (NDT), abdominal hollowing, abdominal bracing, and conventional therapy (Cabanas-Valdés et al, 2013;Lee et al, 2020). NDT is the most studied approach for improving trunk function in hemiplegic stroke.…”
Section: Treatment For Trunk Impairment In Strokementioning
confidence: 99%
“…The mode and efficiency of a person’s gait depend on core and lower limb muscle strength, coordination, and free joint mobility ( 9 , 10 ). Accumulating evidence suggests that exercise interventions, such as muscle strength, endurance, and balance training, can improve gait performance in healthy adults, especially in elderly subjects ( 11 ).…”
Section: Introductionmentioning
confidence: 99%